Alterations in fecal short-chain fatty acids in patients with irritable bowel syndrome: A systematic review and meta-analysis. Issue 7 (February 2019) - Sun, Qinghua; Jia, Qiong; Song, Lijin; Duan, Liping
Abstract: Background: Recent studies indicate that gut microbiota disorders potentially contribute to the pathogenesis of irritable bowel syndrome (IBS), which can be partly reflected by fecal short-chain fatty acids (SCFAs) generated from gut microbiota. Previous studies on SCFA alterations in patients with IBS have yielded conflicting results. No prior systematic review has been conducted on the alterations in fecal SCFAs in IBS patients. Aims: We performed a meta-analysis to explore and clarify alterations in fecal SCFAs in IBS patients. Methods: Case-control studies, randomized controlled trials (RCTs), and self-controlled studies were identified through electronic database searches. The standardized mean difference (SMD) with 95% confidence interval (CI) in fecal SCFA levels between different groups was calculated. Results: The proportion of fecal propionate in patients with IBS was significantly higher than in healthy controls (HCs) (SMD = 0.44, 95% CI = 0.12, 0.76). A subgroup analysis showed that the concentration of fecal propionate (SMD = −0.91, 95% CI = −1.41, −0.41) and butyrate (SMD = −0.53, 95% CI = −1.01, −0.04) in patients with constipation-predominant IBS (IBS-C) was significantly lower than that in HCs, and the concentration of fecal butyrate in patients with diarrhea-predominant IBS (IBS-D) was higher than that in HCs (SMD = 0.34, 95% CI = 0.00, 0.67). Finally, we found that restricted diets correlated with fecal butyrate reduction in IBS (SMD = −0.26, 95% CI = −0.51, −0.01). Conclusions: In terms of fecal SCFAs, there were differences between patients with IBS and HCs. In IBS-C patients, propionate and butyrate were reduced, whereas butyrate was increased in IBS-D patients in comparison to HCs. Propionate and butyrate could be used as biomarkers for IBS diagnosis. Abstract : Supplemental Digital Content is available in the text